Voltammetric determination of lead in vegetable juice samples - Nor, Nor Fatin Ayuni Mohamad (Universiti Sains Malaysia, 2015)
This research investigated lead concentrations in vegetables juices were investigated as they are toxic to our body. The average daily intake of lead in vegetables juices is only 0.5 ppm due to its toxicity to our body. Lead can be adsorbed into vegetables through the water that use for watering the vegetables. It also may come from the water that use to make juice. In this work, the presence of lead levels in vegetables juices such as tomato, pumpkin, winter chestnut, winter melon, carrot, spinach, kale, cabbage, mustard, and eggplant were determined by Differential Pulse Anodic Stripping Voltammetry (DPASV) after wet digestion of the organic matter. Standard addition method was used for this analysis. Parameters used for DPASV were as follows, start potential: -0.599 V, end potential: -0.199 V, deposition time: 60 s, equilibrium time: 10 s, voltage step: 0.005951 V, voltage step time: 0.15 s, sweep rate: 0.0397 V/s, pulse amplitude: 0.05005 V, pulse time: 0.04 s.The result of lead concentration in tomato, pumpkin, carrot, spinach, kale, cabbage, mustard, and eggplant were 24.455 ppb, 18.755 ppb, 11.420 ppb, 0.440 ppb, 2.850 ppb, 6.155 ppb, 5.392 ppb and 3.164 ppb respectively. Lead was not detected in winter chestnut and winter melon juices.